PERBEDAAN PENGARUH METODE LATIHAN SIRKUIT DAN METODE LATIHAN SENAM KEBUGARAN JASMANI (SKJ 2012) TERHADAP PENINGKATAN KEBUGARAN JASMANI - Nofrizal, Dedi (Jurnal Curricula, 2016)
AbstractThe problem of this research is the low level of physical fitness students of SMAN 1 West Sumatra. This research’s purpose is to know the effect of circuit training method and SKJ 2012 training method on increasing physical fitness of the students of SMAN 1 West Sumatra.The method used in this research is quasi experimental, revealing the design of circuit training method and SKJ 2012 training method. The sample is 40 students of  SMAN 1 West Sumatra.The sampling technique used is purposive sampling. After a pre-test, the samples was divided into two group, the circuit training method group and SKJ 2012 training method group. Each group consisted of 20 students. Treatments were done 16 times with training frequency at three times a week. Training duration was ± 120 minutes every meeting. The instrument used to measure the student’s level of physical fitness is TKJI test. Hypothesis 1 and 2 used data analysis of dependent sample t-test and hypothesis 3 used independent sample t- test. The results shows that: 1) circuit training method has significant effect on physical fitness, the average score increased from 13,20 in pre-test increased by 4,05 become 17,25 in post-test, also the statistic results show that (tcount 20,419 > ttable 1,72).  2) SKJ 2012 training method has significant effect on physical fitness, the average score increased from 12,85 in pre-test increased by 2,45 becomes 15,30 in post-test with (tcount 15,964 > ttable 1,72). 3) There is a difference between Method Effect of Exercise Circuit and Method of Physical Fitness Exercise (SKJ 2012) Toward Improved Physical Fitness, where (tcount 6,380 > ttable 2,03). In looking at the magnitude of the mean, mean turns Circuit Training Method larger than the mean Physical Fitness Exercise Method (SKJ 2012) (17,25> 15,30) this means that more effective method Circuit Exercise Improves Physical Fitness a student. Keywords : Circuit Training Method, SKJ 2012 Training Method, Increasing Physical Fitness